IMPLEMENTASI MODEL PAIKEM DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA di SMP NEGERI 46 PALEMBANG - Fathia Tiara Mulyana; Kurnisar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the implementation of the PAIKEM model in improving the critical thinking skills of students at SMP Negeri 46 Palembang. This study employs a qualitative approach using a descriptive method. The sampling technique used in this study is purposive sampling, with one primary informant and 36 research subjects. Data collection techniques include documentation, tests, and interviews. Data analysis techniques used in this study include data presentation and conclusions. Based on the results of this study, it was found that: the implementation of the PAIKEM model had a significant positive impact on improving students' critical thinking skills in Pancasila education. This was reflected in the gradual increase in students' test scores from the first meeting (average 69.57%) to the second meeting (average 82.06%) and the third meeting (average 88.94%). This study concludes that the PAIKEM model is effective in increasing students' active involvement in the learning process, creating a pleasant learning atmosphere, and developing critical thinking skills, particularly in analyzing, evaluating, and creating solutions to problems related to the learning material. However, the implementation of the PAIKEM model still faces various challenges, such as the limited time available for learning in the classroom.